ENCOURAGING SELF-REGULATED LEARNING IN VISUAL ARTS: ITS EFFECTS ON STUDENT ATTITUDE AND PERFORMANCE. - Carvalho, Marina (2016)
There is considerable research evidence on the effectiveness of self-regulated learning (SRL) approaches in classroom practice across subject areas and educational stages. Notwithstanding, because the holistic approach of SRL entails a complex web of dynamics and a number of strategies and concepts to grasp, it is far from being a ready-made recipe. This conclusion leads to two questions: What is the potential of SRL in the development of more autonomous and self-directed learners, and how can SRL be effectively implemented in classroom practice? Against this background, the present study takes a practice-based inquiry (PBI) approach to investigating SRL strategies within visual arts learning in middle school, and its effects on student attitude and performance, by: 1) looking closely at the structure of SRL; 2) identifying students’ cognitive, metacognitive, and motivational weaknesses in visual arts learning; and 3) proposing the guidelines for an SRL programme to enable and encourage students to become more autonomous and self-directed learners. Informed by the literature, this work examines the historical background and context of SRL theories and the relevancy of: 1) cooperative learning; and 2) assessment for learning approaches within SRL implementation. The methodology of this PBI is developed within an action research approach that includes the collection of triangulated data, a teacher focus group, and investigator triangulation. The successes and limitations of the PBI and the implementation of the SRL programme guidelines are reviewed, followed by a reflection on present and future challenges that need to be addressed. As a result, the study finds that, although this PBI strengthened several aspects within the teacher-student dynamic and teacher collaboration, and although the SRL programme guidelines stand as a promising plan that the school is willing to implement, issues pertaining to the specificities of participatory research and the cultural context of both the students and school present great challenges to be addressed.